Multimodal displays of understanding in vocabulary-oriented sequences - Gudmundsen, Jenny; Svennevig, Jan (Social Interaction. Video-Based Studies of Human Sociality, 2020)
How do participants use multimodal means to display joint understanding after dealing with vocabulary problems in second language interactions? In this article, we investigate the resolution phase of vocabulary-oriented sequences, more specifically word searches, word explanation sequences and vocabulary checks. We argue that understanding is displayed not only by change-of-state tokens, but typically by a more encompassing multimodal gestalt involving facial expression, gestures, and torso movements. A central feature of this gestalt is what we propose to call the change-of-state face, which consists in raised eyebrows and widened eyes and is produced while the head and/or the torso is raised upwards. Typically, this display of a change-of-state is followed by further demonstrations of understanding, such as verbal and gestural repeats. Finally, the solution of the problem is often ‘celebrated’ by means of reciprocal smiling. Not all vocabulary-oriented sequences are equally successful. Facial expression and gesture may also be used to resist and question a proposal of a candidate solution to a word search or a request for an explanation. In this way, multimodal means are crucial to establishing the success of vocabulary-oriented sequences and returning to the main business of the talk.